Correlation between the factors of unsafe acts and unsafe conditions and the occurrence of work accidents among construction workers (a case study of PT X at Hospital Y project) - Nabila, Salwa Putri Nabila; Widowati, Evi (Periodicals of Occupational Safety and Health, 2022)
Backgrounds: Generally speaking, unsafe acts and unsafe conditions are the causes of work accidents. Based on the HSE reports, the cases of occupational accidents in the Hospital Y project in the last 7 months until October 2021 had amounted to 20. The correlation between the unsafe acts as well as unsafe conditions and the occurrence of work accidents constitutes the basis and objectives of this study. Methods: This study is quantitative in nature, with analytical observation implementing cross sectional approach. It involved 63 out of 130 workers (consisting of staff, supervisors, and subcontractor workers) who were selected using purposive sampling technique. Instruments in the forms of questionnaires, observations, and documentary studies were implemented. The data were further analyzed using chi-square test, fisher test, and cell pooling. Results: It was shown from the statistics that the Occupational Safety and Health (OSH) Knowledge gained the score of (p=0,066; PR=1,368; 95%CI=0,995-1,879), Load of Work (p=0,010; PR=0,647; 95%CI=0,457-0,916), OSH Training (p=0,029; PR=1,833; 95%CI=0,873-3,848), Equipment Safety Gear (p=0,005; PR=1,682; 95%CI=1,102-2,567), and Operational Procedures (p=<0,0001; PR=1,934; 95% CI=1,251-2,991). Conclusions: It is found that no correlation was existent between OHS Knowledge occurrence of work accidents. However, there was a correlation between work load, OSH training, and equipment safety gear and the occurrence of work accidents.